2021
DOI: 10.1155/2021/6942497
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Algorithms and Visual Inspection for Detection of Trigger Asynchrony in Critical Patients : A Systematic Review

Abstract: Objective. This study aimed to summarize the accuracy of the different methods for detecting trigger asynchrony at the bedside in mechanically ventilated patients. Method. A systematic review was conducted from 1990 to 2020 in PubMed, Lilacs, Scopus, and ScienceDirect databases. The reference list of the identified studies, reviews, and meta-analyses was also manually searched for relevant studies. The reference standards were esophageal pressure catheter and/or electrical activity of the diaphragm. Studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Recently, many dedicated machine-learning software designed to continuously detect patient ventilator asynchrony have been developed. A systematic review demonstrated that these algorithms or software had high sensitivity and specificity to detect patient ventilator asynchrony compared to the reference standard using P es or EAdi [ 25 ]. IntelliSync + software (Hamilton Medical AG, Bonaduz, Switzerland) is a new technology to detect the initiation and the end of inspiration by analyzing P aw and airflow waveforms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many dedicated machine-learning software designed to continuously detect patient ventilator asynchrony have been developed. A systematic review demonstrated that these algorithms or software had high sensitivity and specificity to detect patient ventilator asynchrony compared to the reference standard using P es or EAdi [ 25 ]. IntelliSync + software (Hamilton Medical AG, Bonaduz, Switzerland) is a new technology to detect the initiation and the end of inspiration by analyzing P aw and airflow waveforms.…”
Section: Discussionmentioning
confidence: 99%